Legal Accountability for the Utilization of Autonomous Cyber Defense Systems in Cybersecurity Governance - Yovid; Marhaeni Ria Siombo (Journal Customary Law, 2026)
The increasingly complex development of cyber threats has driven the use of artificial intelligence-based cyber defense technology capable of autonomous operation, known as Autonomous Cyber Defense Systems (ACDS). These systems offer high efficiency and speed of response, but also raise new legal issues related to accountability for actions resulting from algorithmic decisions. This study aims to analyze the nature of legal accountability problems in the use of ACDS and examine the limitations of the legal framework that is oriented towards human subjects. The study focuses on the unclear legal subjects responsible, the difficulty of tracing system decisions, and the potential for human rights violations resulting from automated cyber defense actions. The research method employs normative legal research through legislative, conceptual, and comparative approaches. The analysis was conducted on national regulations related to cybersecurity, electronic systems, and personal data protection, as well as international principles and soft law relevant to the governance of artificial intelligence and cybersecurity. The results reveal that conventional legal approaches are inadequate to address accountability challenges in autonomous cyber defense systems due to the limitations of traditional responsibility doctrines. This study proposes the reconstruction of an adaptive and layered legal accountability model by strengthening the principles of human oversight, algorithmic transparency, and the division of responsibility between actors. This model is expected to serve as a normative basis for developing effective, equitable, and human rights-compliant cybersecurity governance in the digital age.